Ethno-Economics in Action: The Case of Tuva and Altai. Issue 1 (4th May 2021) - Madiukova, S.A.; Persidskaia, O.A.
ABSTRACT: This article examines the ethno-economic structure's potential for the development of regional economic models, as well as the specific forms and practices of ethno-economic neotraditionalism in the life of ethnic groups in the Tuva and Altai republics. We consider specific ethnocultural traditions and traditional livelihood of Tuvan and Altai peoples as resources for increasing regional economic stability. On the other hand, our analysis of the ways neotraditionalism manifests allows us to document such neotraditional trends as rationalization and commercialization of the traditional and the tendency to replace authentic culture with ersatz forms. We identify the specific spheres in and mechanisms by which the traditional is monetized: ethno-tourism and traditional environmental management, ethno-cuisine and ethno-fashion, throat-singing as a brand, and the noncompetitiveness of ethnic languages.